Toward Good Simulation Practice Best Practices for the Use of Computational Modelling and Simulation in the Regulatory Process of Biomedical Products - Viceconti, Marco; Emili, Luca (Synthesis Lectures on Biomedical Engineering,, 2024)
This open access book, the Community of Practice led by the VPH Institute, the Avicenna Alliance, and the In Silico World consortium has brought together 138 experts in In Silico Trials working in academia, the medical industry, regulatory bodies, hospitals, and consulting firms. Through a consensus process, these experts produced the first attempt to define some Good Simulation Practices on how to develop, evaluate, and use In Silico Trials. Good Simulation Practice constitutes an indispensable guide for anyone who is planning to engage at any title with In Silico Trials. This book is open access, which means that you have free and unlimited access. Offers readers a unique guide to In Silico Trials Documents consensus process run by the most authoritative organizations worldwide in the field Represents the first attempt to produce a consensus position on the best practice for In Silico Trials.